Visual search for emotional faces in children - Waters, A.; Lipp, Ottmar (Routledge, 2008)
The ability to rapidly detect facial expressions of anger and threat over other salient expressions has adaptive value across the lifespan. Although studies have demonstrated this threat superiority effect in adults, surprisingly little research has examined the development of this process over the childhood period. In this study, we examined the efficiency of children's facial processing in visual search tasks. In Experiment 1, children (N=49) aged 8 to 11 years were faster and more accurate in detecting angry target faces embedded in neutral backgrounds than vice versa, and they were slower in detecting the absence of a discrepant face among angry than among neutral faces. This search pattern was unaffected by an increase in matrix size. Faster detection of angry than neutral deviants may reflect that angry faces stand out more among neutral faces than vice versa, or that detection of neutral faces is slowed by the presence of surrounding angry distracters. When keeping the background constant in Experiment 2, children (N=35) aged 8 to 11 years were faster and more accurate in detecting angry than sad or happy target faces among neutral background faces. Moreover, children with higher levels of anxiety were quicker to find both angry and sad faces whereas low anxious children showed an advantage for angry faces only. Results suggest a threat superiority effect in processing facial expressions in young children as in adults and that increased sensitivity for negative faces may be characteristic of children with anxiety problems.